COPHYD (Corona Owed Physical Deficiency): The Impact of Lockdown on Cardiopulmonary Function in Paediatric Cardiology Patients - Stabler, Tim; Weigelt, Annika; Rottermann, Kathrin; Wällisch, Wolfgang; Hübner, Matthias; Dittrich, Sven; Schöffl, Isabelle (Klinische Pädiatrie, 2022)
Introduction Due to the Corona-lockdowns the closure of sports facilities and schools has led to a decline in physical activity (PA) for months. PA is essential for maintaining cardiopulmonary function assessed by peak oxygen uptake. Since peak oxygen uptake represents the best predictor for mortality and morbidity in children with congenital heart disease the impact of lockdowns on this parameter is vital. Methods We evaluated retrospectively cardiopulmonary exercise data from our patient collective from before lockdown with twin-paired data from during lockdown. The twin-pairing was achieved by matching patients with similar heart disease, age, sex, and test method. Cardiopulmonary exercise testing was achieved on either the treadmill or the bicycle. Results We were able to twin-pair 90 cases (26 twins with heart disease and 19 healthy twins). There was a significant decrease of cardiopulmonary function (V?O (2) peak: 35.7 +/- 9.8 vs.30.4 +/- 10.6) in the heart disease cohort along with a significant decrease in peak oxygen pulse (13.3 +/- 4.1 vs. 11.4 +/- 4.5), and peak minute ventilation (V ?E: 83.05 +/- 29.08 vs.71,49 +/- 24.96). The healthy children improved over the timeframe, but this only reached significance for peak minute ventilation (81.72 +/- 25.79 vs.97.94 +/- 31.4). Conclusion We observed a significant decline of peak oxygen uptake during lockdown in the group of congenital heart disease (CHD) patients. This involved a loss of cardiac function as well as pulmonary function. This could be explained by limited access to sports facilities and restriction of regular daily movement due to school closure and overprotection. Healthy children improved their pulmonary function. This might be an indication of an improvement of exercise during confinement.
CRIS-Team WoS Importer:2022-10-14